In vitro Appraisal of Interactions between Spot Blotch Pathogen B. sorokiniana and Selected Parasitic Fungi of Wheat Leaves - Ranamukharachchi, Deepak Bhandari*; S. L. (Journal of Phytology, 2010)
Pathogenic micro-organisms living on wheat foliages may interact with each others. This study was conducted to reveal the interactive relationships existing between spot blotch causing fungus Bipolaris sorokiniana and selected pathogenic fungi subsisting on wheat foliages. Four fungal pathogens of wheat were selected, and the intensity and severity of the selected pathogenic fungi on wheat leaves were assessed. Pure cultures of the fungi were produced by isolating them from the spot blotch infected and blighted wheat leaves. Separate in vitro dual culture studies in completely randomized design with five replications were carried out to assess the interactions between each pair of B. sorokiniana and selected rival pathogens of wheat foliages. Percent inhibition in radial growth of either fungus was calculated. Viability test of the mycelium at the interface zone and pathogenicity test of the isolates were carried out. B. sorokiniana strongly inhibited the colony growth of Cercospora sp. and Phoma sp. under in vitro conditions. Similarly, there was not any effect on colony growth of either B. sorokiniana or Bipolaris sp. due to dual culture with each other. The dual culture of B. sorokiniana and Alternaria triticina results in the suppression of colony growth of both fungi. There were non-significant differences in percent growth inhibition between the first and the second week of dual culture in some of the tested fungi.Â The viability of mycelia of all the tested fungi was intact in dual culture. B. sorokiniana exerts antagonistic ability against some minor pathogens of wheat foliages under in-vitro conditions.Â